Konsep Pemikiran Ibnu Miskuwaihi tentang Pendidikan Akhlak dan Relevansinya dengan Dunia Pendidikan Islam di Masa Modern - Hoirul Anam; Zulkipli Lessy (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
at this time moral abominations are rampant in the midst of society, as if there is no attempt to overcome them. Education which is considered as a reference in printing the nation's moral generation, now seems to be just a name, because moral decline does not only occur among the uneducated, but many students also participate in it. even bad morals also arise from educational institutions. so the author conducts research by adopting the title of the concept of Ibn Miskuwaihi's thoughts on moral education and its relevance to the world of Islamic education in modern times. The research method used by the author uses descriptive qualitative research in the type of literature review, namely research that only focuses on finding the necessary data, by focusing on library research, with the aim of being able to know the concept of Ibn Miskuwaihi's thinking in shaping moral character, as well as its relevance to world of Islamic education in this modern era. The results of this study are three things, firstly the concept of Ibn Mikuwaihi's thought as a guide that must be adhered to by educators, as well as educators to deal with all things that are demands in this modern era, secondly, moral education is not only improving morals between fellow humans, but the moral education proposed by Ibn Miskuwaihi can also improve morals with Allah SWT, who can create modern humans with all forms of progress. The three moral education in its application are not limited by space and time while there are moral abominations, especially in this modern era where despicable morals are rampant like in the time of Ibn Miskuwaihi.